Larval breeding habitats and ecological factors influence the species composition of mosquito (Diptera : Culicidae) in the parks of Dhaka city, Bangladesh (Bangladesh Journal of Zoology, 2018)
Mosquito larval ecology is prerequisite for determining the larval abundance and species assemblage in mosquito control program. The study explored the association of five mosquito species with their breeding habitat diversity and species distribution in three selected parks from May to October, 2015. A total of 3217 mosquito larvae were reported from six breeding habitats, namely tree hole, leaf axils, water bottle, tire, drain and coconut shell. The frequency of the three species (Ae. aegypti, Ae. albopictus and Ar. subalbatus) coexistence was higher in tree holes (82.4%) than that of the other coexisting species. Pearson Chi-square result revealed that the association of species was significantly dependent on the breeding habitats. ANOVA further suggested that mosquito density varied across habitats where among the highest density of Cx. quinquefasciatus (3.87 ± 0.22) found in drain, followed by both Ae. albopictus (2.02 ± 0.17) and Ar. subalbatus (0.50 ± 0.09) in tree holes and Ae. aegypti (1.25 ± 0.23) in coconut shell. Cx. tritaeniorhynchus occurred in drain with the least observed density (0.03 ± 0.01). CCA results suggested that Aedes species were likely preferred to oviposit in shaded habitats where pH was associated with Ae. albopictus and dissolved oxygen was with Ae. aegypti and Ar. subalbatus. Culex species were positively associated with the habitats characterizing muddy bottom and emerging vegetation but not with any of the physico-chemical parameters. These findings concluded that ecological factors influence mosquito species to favor their breeding habitats can be helpful in controlling targeted vector species as well as the mosquito borne diseases.Bangladesh J. Zool. 45(2): 111-122, 2017